2006
DOI: 10.1111/j.1463-1318.2006.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation induces pan‐colonic propagating pressure waves and increases defecation frequency in patients with slow‐transit constipation

Abstract: These data demonstrate that SNS induces pan-colonic propagating pressure waves and therefore shows promise as a potential therapy for severe refractory constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 54 publications
5
140
0
4
Order By: Relevance
“…13 The delay in colonic transit caused by the denervated colon following ASCI is one of the reasons for constipation, 14 whereas SNS promotes colon mobility, and increases luminal transport and defecation. 15,16 Our studies have further confirmed that endotoxemia and bacterial translocation from the gut occurs after ASCI. These alterations are in part consistent with the findings reported by Liu and colleague.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…13 The delay in colonic transit caused by the denervated colon following ASCI is one of the reasons for constipation, 14 whereas SNS promotes colon mobility, and increases luminal transport and defecation. 15,16 Our studies have further confirmed that endotoxemia and bacterial translocation from the gut occurs after ASCI. These alterations are in part consistent with the findings reported by Liu and colleague.…”
supporting
confidence: 63%
“…18 Electrical stimulation of the 3rd sacral nerve has been shown to induce pan-colonic propagating pressure waves and significantly increase pan-colonic antegrade propagating sequence frequency, which increased stool frequency and quantity. 15 Therefore, electrical stimulation of the 3rd sacral nerve promotes intestinal motility, and improves the function of the digestive tract. The stimulation increases luminal transport and defecation, and decreases the levels of endotoxin and the rate of gut bacterial translocation.…”
mentioning
confidence: 99%
“…Stimulation of the corresponding points on the head (GV20 or EX-PN1) and back (BL23, BL25, and BL31-34, from the first to the fourth sacral foramen, respectively) and abdomen (ST25, SP14, SP15, CV4, and CV6) will modulate the intestinal function. It has been proven that stimulation of the sacral nerve can promote colonic motility, and improve pelvic floor sensation [17,51]. Brain imaging studies have demonstrated two potential routes of pain modulation by acupuncture via deactivation of descending nociceptive pathways and by decreased limbic activity during acupoint stimulation [52].…”
Section: Difference Of Effectsmentioning
confidence: 99%
“…These include stapled transanal rectal resection (STARR) [26,27], Transtar, laparoscopic ventral rectopexy [28], and sacral nerve stimulation [17,29], which have some benefits. However, these approaches are still associated with a significant expense and potential morbidity [30].…”
Section: Obstructive Defecation Syndrome (Ods)mentioning
confidence: 99%
See 1 more Smart Citation